MEKANISME PEMBIAYAAN PEMILIKAN RUMAH iB MASLAHAH DENGAN AKAD MURABAHAH DI BANK BJB SYARIAH KANTOR CABANG BOGOR - Ariyo Bimo, Widhi; Maryam, Siti (Fakultas Ekonomi dan Bisnis Universitas Ibn Kahldun Bogor, 2020)
One of the primary human needs besides clothing and food is shelter, namely a place to live (house), along with the changing times the need for a proper place to live (house) has become a necessity. Having a proper place to live (house) is a dream for all humans, to have a proper place to live (house) requires several requirements and of course through the existing mechanisms. Bank financial institutions can be partners and solutions in meeting the need for a decent place to live (house). The existence of home ownership financing products in Islamic Banking has provided an alternative to housing financing that is free from usury (interest). One of them is the Murabahah contract which provides certainty about the amount of installments that the customer must pay each month. The purpose of this study is to find out the iB Maslahah Home Ownership Financing Mechanism with the Murabahah Agreement at Bank Jabar Banten Syariah Bogor Branch Office, the results show that the Ownership Financing Mechanism Rumah iB Maslahah With Murabahah Agreement at Bank Jabar Banten Syariah Bogor Branch Office promotes halal and good investment and produces the expected return, in channeling its financing always prioritizes the aspects of Sharia, always observes the systems and financing procedures used in accordance with standard operating procedures and operational standards management.